Answer:
-35
Step-by-step explanation:
-5 (x + 2) + 5 (x -5)
Expand:
= -5x - 10 + 5 (x - 5)
Expand once more:
= -5x - 10 + 5x - 25
Simplify:
-35
9x^2+t+25=(ax+b)^2
9x^2+t+25=a^2*x^2+2abx+b^2 so
a^2=9 so a=3
b^2=25 so b=5 then
t=2ab using a and b from above
t=2*3*5=30
So the missing term is 30x
Answer: d
Step-by-step explanation:
Find the area of the rectangle.
Find the area of the base of the semicircle.
12 in would be the diameter, divide by 2 to get the radius.
Plug this into the formula.
Since we do not have a full circle but a semi one instead, we must divide our result by 2.
Add both areas.
180+56.52=236.52
Answer:
c.) 4 2/3
Step-by-step explanation:
look at the screenshot below it'll explain the answer
Solution
-6x - 3y = 9 Add 6x to both sides
-6x + 6x - 3y = 9 + 6x
-3y = 9 + 6x Or more conventionally
-3y = 6x + 9 Divide by - 3
y = 6x/-3 + 9/-3
y = - 2x - 3